2006
DOI: 10.2106/jbjs.e.00878
|View full text |Cite
|
Sign up to set email alerts
|

Revision Total Elbow Arthroplasty for Prosthetic Fractures

Abstract: Therapeutic Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Although these complications are rare, the authors concluded that component fracture may be related to notch sensitivity, component design, and high stresses due to bone deficiency. 4 Previously, our patient had a fall and required revision TEA for a fractured humeral component. In addition to the direct impact at the elbow, compromised integrity of her osseous tissue may have also contributed to undue component stress.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Although these complications are rare, the authors concluded that component fracture may be related to notch sensitivity, component design, and high stresses due to bone deficiency. 4 Previously, our patient had a fall and required revision TEA for a fractured humeral component. In addition to the direct impact at the elbow, compromised integrity of her osseous tissue may have also contributed to undue component stress.…”
Section: Discussionmentioning
confidence: 94%
“…4,14,17,22 Certainly, the potential exists that a combination of these factors contributed to the acceleration of our patient's extensive bone loss and compromised bone stock. Athwal and Morrey 4 have previously reported humeral and ulnar fracture rates of 0.65% and 1.2%, respectively, after primary TEA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…• Periprosthetic fractures with a well-fixed component may require cortical allograft struts and band- ing for reconstruction. 6,7 Periprosthetic fractures with a loose component require revision with a longer stem, as well as cortical allograft struts and banding. Surgery for a loosened component before periprosthetic fracture will require revision of the component, as well as possible impaction bone grafting for intramedullary bone loss.…”
Section: Pearls and Pitfallsmentioning
confidence: 99%
“…According to 1 series, the prevalences of humeral and ulnar component prosthetic elbow fracture were 0.65% and 1.2%, respectively. 40 Periprosthetic fractures in which the components are stable can be treated nonsurgically or by open reduction with internal fixation. For unstable components, revision arthroplasty with conversion to a longer stem should be performed.…”
Section: Figurementioning
confidence: 99%